2021
DOI: 10.3390/ijerph18010357
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Red and Processed Meat Consumption across North America: A Nationally Representative Cross-Sectional Comparison of Dietary Recalls from Canada, Mexico, and the United States

Abstract: Close economic ties encourage production and trade of meat between Canada, Mexico, and the US. Understanding the patterns of red and processed meat consumption in North America may inform policies designed to reduce meat consumption and bolster environmental and public health efforts across the continent. We used nationally-representative cross-sectional survey data to analyze consumption of unprocessed red meat; processed meat; and total red and processed meat. Generalized linear models were used to separatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 29 publications
1
36
0
1
Order By: Relevance
“…In assessing adherence to an MSDP, the current study offers supplemental guidance to the DGA to show how much Americans continue to overconsume certain food groups ( 42 ). Considering a score of 10 for each food group equates meeting the recommend MSDP amounts, the HA and nHA mean scores for meat (0.39 ± 0.04 and 0.17 ± 0.01, respectively) and added sugars (0.14 ± 0.02 and 0.04 ± 0.01, respectively) illustrate a critical need for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In assessing adherence to an MSDP, the current study offers supplemental guidance to the DGA to show how much Americans continue to overconsume certain food groups ( 42 ). Considering a score of 10 for each food group equates meeting the recommend MSDP amounts, the HA and nHA mean scores for meat (0.39 ± 0.04 and 0.17 ± 0.01, respectively) and added sugars (0.14 ± 0.02 and 0.04 ± 0.01, respectively) illustrate a critical need for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of studies conducted in the United States, Canada, and Mexico in 2013–2016 showed that the consumption of red and processed meat was high in all these countries [ 48 ]. The median intake of unprocessed red meat estimated using cooked weight in Canada was 79.0 g/day; in the US, it was 72.3; and in Mexico, it was 62.0 g/day.…”
Section: Discussionmentioning
confidence: 99%
“…The highest number of male respondents from this cluster declared that if they are having a dessert at home, they try to have something low in fat, while the highest number of female respondents from this cluster declared that they usually avoid eating fried foods, declared that they usually choose the healthiest dessert or pudding in a restaurant, and denied including chocolate and/or biscuits in a packed lunch, comparing to the other clusters. It should be indicated that the described differences may result from the general gender-dependent preferences and intake of food products—higher intake of meat for men [ 52 ] and sweets for women [ 16 ], which corresponds the fact that only in the case of the ‘low-preferring’ cluster, female respondents declared reduced desserts consumption and choosing the healthiest one.…”
Section: Discussionmentioning
confidence: 99%